Role of high sensitivity cardiac troponin assays in the assessment and experience of patients presenting to the Emergency Department with suspected acute coronary syndrome - Ferry, Amy Victoria (The University of Edinburgh, 2019)
The improved precision of high-sensitivity cardiac troponin (hs-cTnI) assays has enabled two advances in the assessment of patients with suspected acute coronary syndrome; 1) the use of sex-specific criteria for the diagnosis of myocardial infarction, and 2) the development of pathways to identify low risk patients in the Emergency Department setting, who may be suitable for immediate discharge. This thesis had two overarching aims: to explore the gendered dimensions of the new assessment process and to examine how patient experience of chest pain may be shaped by the implementation of an early rule-out pathway for myocardial infarction. In order to achieve these, the study had two components: a quantitative analysis of the presenting characteristics of men and women diagnosed with myocardial infarction using sex-specific criteria, and a qualitative interview study with patients who experienced assessment either before or after implementation of an early rule-out pathway. In the quantitative element of this thesis, I aimed to determine the frequency and predictive value of presenting characteristics in patients with myocardial infarction by evaluating patient reported symptoms in 1,941 patients (39% women) with suspected acute coronary syndrome. Typical symptoms were more common in women than men with myocardial infarction (77% [69/90] versus 59% [109/184], P=0.007), and were similar in those women and men who were reclassified with myocardial infarction due to the use of sex-specific criteria (74% [20/27] versus 44% [4/9], P=0.22). In women, the combination of three or more typical features was associated with a significantly positive likelihood ratio for a diagnosis of myocardial infarction (LR+1.18, 95% CI 1.03 to 1.31), but this relationship was not observed in men (LR+ 1.09, 95% CI 0.96 to 1.24). The improved precision of the hs-cTnI assay has enabled the diagnosis of myocardial infarction to be excluded in the Emergency Department without requiring hospital admission. Understanding the patient experience of earlier clinical decisions will ensure these new diagnostic pathways benefit both the healthcare system and patients themselves. The qualitative element was designed to explore how patient experience of chest pain may be shaped by the implementation of an early rule-out pathway. Patients attending the Emergency Department who had myocardial infarction ruled out were eligible for inclusion. Purposive sampling was used to ensure representation across age and sex categories. 23 participants were interviewed before, and 26 participants were interviewed after implementation of the early rule-out pathway one week following discharge. The content of participant accounts did not appear to be dictated by whether they were assessed before or after implementation of the early rule-out pathway with many common themes arising from both pathways. Patient experience of chest pain extended both before and after the in-hospital period revealing a phased illness episode. Participants described how they appraised their symptoms involving a complex process of interpretation and evaluation of the appropriate action. Patient accounts also revealed the differing priorities of the clinical pathway (the rule-out of myocardial infarction) to the holistic patient view desired by participants themselves. The confirmation of the absence of disease did not provide all patients with the reassurance that they desired. Providing pre-test information regarding the troponin test, in addition to active listening and the building of a trustful clinician-patient relationship appeared to relate to positive expressions of reassurance within participant accounts. Following discharge, participants had to continue to make sense of their chest pain experience. The way in which some participants made use of their acute chest pain presentation to hospital as an opportunity to consider their future heart health emerged as an unelicited theme. Participants assessed using the early rule-out pathway appeared to have a lesser orientation to use the episode of chest pain as a cue to action to appraise their future health status. The findings of this thesis suggest that high-sensitivity cardiac troponin assays will aid the assessment of patients with suspected acute coronary syndrome in two important ways. Firstly, the clinical significance of typical symptom clusters and their correlation to myocardial infarction in women is highlighted. Secondly, the successful implementation of early rule-out pathways into the Emergency Department will be aided by the addition of simple communication interventions during the chest pain assessment process. Extending the focus of assessment beyond the rule-out of myocardial infarction may enhance the care experience of patients. This thesis has also demonstrated how qualitative research has provided a mechanism through which to explore how the biochemical evidence of the early rule-out pathway may be applied in a clinical environment, enabling the application of trial data into a real-life clinical context that responds to patients’ needs.
Keywords: acute coronary syndrome; sex; qualitative research; interviews; chest pain